Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis